Pancoast Tumor: The Role of Magnetic Resonance Imaging - Guglielmo Manenti; Mario Raguso; Silvia D'Onofrio; Simone Altobelli; Angela Lia Scarano; Erald Vasili; Giovanni Simonetti (Case Reports in Radiology)
We report imaging techniques in the definition of the therapeutic planning of a 65-year-old man with a diagnosis of Pancoast tumor. Computed Tomography has a pivotal role in the assessment of nodes involvement and distant metastasis. Magnetic Resonance allows a detailed study of locoregional extension for its high soft tissue resolution. We particularly highlight the actual importance of Magnetic Resonance Neurography, Diffusion-Weighted Imaging, and Magnetic Resonance Angiography techniques in the assessment of the superior sulcus vascular and nervous structures involvement. Their integrity has been showed in our patient with a complete surgical excision of the lesion.